2016
DOI: 10.1021/acsami.6b09642
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric Polymer Scaffolds Filled with Azobenzene-Containing Nematic Mixture with Phototunable Optical Properties

Abstract: The past two decades witnessed tremendous progress in the field of creation of different types of responsive materials. Cholesteric polymer networks present a very promising class of smart materials due to the combination of the unique optical properties of cholesteric mesophase and high mechanical properties of polymer networks. In the present work we demonstrate the possibility of fast and reversible photocontrol of the optical properties of cholesteric polymer networks. Several cholesteric photopolymerizabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The main feature of 6DABU is reversible E-Z isomerization leading to extreme decrease in molecular anisometry (see Figure 2a). As it was shown before, [24] irradiation of the 5CB+6DABU mixture by UV light induces isothermal phase transition from the nematic phase to the isotropic phase (see Figure 2b). Due to the presence of lateral methyl substituents in azobenzene chromophores, photoinduced Z isomer possesses high thermal stability, thus back transition from isotropic to nematic phase occurs very slowly with characteristic time of about 20 days.…”
Section: Introductionsupporting
confidence: 72%
“…The main feature of 6DABU is reversible E-Z isomerization leading to extreme decrease in molecular anisometry (see Figure 2a). As it was shown before, [24] irradiation of the 5CB+6DABU mixture by UV light induces isothermal phase transition from the nematic phase to the isotropic phase (see Figure 2b). Due to the presence of lateral methyl substituents in azobenzene chromophores, photoinduced Z isomer possesses high thermal stability, thus back transition from isotropic to nematic phase occurs very slowly with characteristic time of about 20 days.…”
Section: Introductionsupporting
confidence: 72%
“…Light is a well‐known external stimulus that can be controlled sequentially, remotely, and rapidly . Photochromic molecules have been intensively studied for their significances in scientific studies and real applications . Owing to the resolved photoisomerization between trans ‐ and cis ‐form, azobenzene is perhaps the most common moiety to produce dramatic changes at molecular order and macroscopic dimensions .…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature also unequivocally demonstrates that nonreactive liquid crystals can swell liquid crystal networks only up to a certain threshold, and this partial miscibility decreases markedly once the azobenzene has switched to the cis form 47,48 . Ryabchun et al 47 have shown how a liquid crystal gel with a low polymer content expels a free liquid crystal doped with azobenzenes upon irradiation with light. Broer et al have reported that azobenzeneactivated smectic gels behave as photo-sponges, because of a photo-induced miscibility with the liquid crystal solvent.…”
Section: Resultsmentioning
confidence: 96%